A nanostructured Fc(COCH3)2 film prepared using silica monolayer colloidal crystal templates and its electrochromic properties. Issue 45 (13th November 2017) - Hua, Chunxia; Dou, Shuliang; Xu, Hongbo; Hou, Shuai; Zhang, Hangchuan; Zhang, Panpan; Gan, Yang; Zhao, Jiupeng; Li, Yao
Abstract : Since oxidation and reduction reactions mainly take place on surfaces, enlarging the specific surface of redox materials is the key to achieving excellent electrochemical performance. Abstract : Since oxidation and reduction reactions mainly take place on surfaces, enlarging the specific surface of redox materials is the key to achieving excellent electrochemical performance. In this work, by using silica monolayer colloidal crystal templates (MCCTs), a nanostructured Fc(COCH3 )2 film is prepared successfully, and such a nanostructure could exhibit the following unique electrochemical properties: the MCCTs could impede the aggregation tendency of Fc(COCH3 )2 and possess high electrochemical activity; Fc(COCH3 )2 enlarges the contact area and offers more active sites and faster electronic transmission channels. The structure, optical and electrochemical properties of the nanostructured Fc(COCH3 )2 were tested and then compared with those of compact Fc(COCH3 )2 films to evaluate the role of the nanoarchitecture. The unique structure design of the Fc(COCH3 )2 film enables outstanding performance, showing a large transmittance change (Δ T ) of 37% at 550 nm when switched between 0.5 V and −2.5 V, which is approximately ninefold higher than that of the compact Fc(COCH3 )2 film (approximately 4%). Response times of coloration and bleaching are found to be only 16.15 s and 5.56 s. Furthermore, the nanostructured Fc(COCH3 )2 film shows much better cycling stability than the compact one. The results indicate that the nanostructure could significantly improve the electrochemical performance of the Fc(COCH3 )2 film due to the increase in electrochemical active sites and the enhancement of the "D-to-A" redox switch of ferrocene.